Diagnosis of Persistent Fever in the Tropics: Set of Standard Operating Procedures Used in the NIDIAG Febrile Syndrome Study. - Emilie Alirol; Ninon Seiko Horie; Barbara Barbé; Veerle Lejon; Kristien Verdonck; Philippe Gillet; Jan Jacobs; Philippe Büscher; Basudha Kanal; Narayan Raj Bhattarai; Sayda El Safi; Thong Phe; et al. (Public Library of Science (PLoS), 2016)
In resource-limited settings, the scarcity of skilled personnel and adequate laboratory facilities makes the differential diagnosis of fevers complex [1-5]. Febrile illnesses are diagnosed clinically in most rural centers, and both Rapid Diagnostic Tests (RDTs) and clinical algorithms can be valuable aids to health workers and facilitate therapeutic decisions [6,7]. The persistent fever syndrome targeted by NIDIAG is defined as presence of fever for at least one week. The NIDIAG clinical research consortium focused on potentially severe and treatable infections and therefore targeted the following conditions as differential diagnosis of persistent fever: visceral leishmaniasis (VL), human African trypanosomiasis (HAT), enteric (typhoid and paratyphoid) fever, brucellosis, melioidosis, leptospirosis, malaria, tuberculosis, amoebic liver abscess, relapsing fever, HIV/AIDS, rickettsiosis, and other infectious diseases (e.g., pneumonia). From January 2013 to October 2014, a prospective clinical phase III diagnostic accuracy study was conducted in one site in Cambodia, two sites in Nepal, two sites in Democratic Republic of the Congo (DRC), and one site in Sudan (clinicaltrials.gov no. NCT01766830). The study objectives were to (1) determine the prevalence of the target diseases in patients presenting with persistent fever, (2) assess the predictive value of clinical and first-line laboratory features, and (3) assess the diagnostic accuracy of several RDTs for the diagnosis of the different target conditions.